DNAJ heat shock protein family member C1 can regulate proliferation and migration in hepatocellular carcinoma - Fan,Yu-Chun; Meng,Zhi-Yong; Zhang,Chao-Sheng; Wei,De-Wei; Wei,Wan-Shuo; Xie,Xian-Dong; Huang,Ming-Lu; Jiang,Li-He (PeerJ, 2023)
Background DNAJ heat shock protein family (Hsp40) member C1(DNAJC1) is a member of the DNAJ family. Some members of the DNAJ gene family had oncogenic properties in many cancers. However, the role of DNAJC1 in hepatocellular carcinoma (HCC) was unclear. Methods In this study, expression and prognostic value of DNAJC1 in HCC were analyzed by bioinformatics. Quantitative real-time PCR and Western blotting were used to verify DNAJC1 expression in liver cancer cell lines. Furthermore, immunohistochemical (IHC) was used to detect DNAJC1 expression in liver cancer tissues. Subsequently, the effect of DNAJC1 on the proliferation, migration, invasion and apoptosis of HCC cells was detected by knocking down DNAJC1. Finally, gene set enrichment analysis (GSEA) was used to investigate the potential mechanism of DNAJC1 and was verified by Western blotting. Results DNAJC1 was highly expressed in HCC and was significantly associated with the prognosis of patients with HCC. Importantly, the proliferation, migration and invasion of Huh7 and MHCC97H cells were inhibited by the knockdown of DNAJC1 and the knockdown of DNAJC1 promoted Huh7 and MHCC97H cell apoptosis. Furthermore, compared to the negative control group, DNAJC1 knockdown in Huh7 and MHCC97H cells promoted the expression of p21, p53, p-p53(Ser20), Bax and E-cadherin proteins, while inhibiting the expression of PARP, MMP9, Vimentin, Snai1, Bcl-2 and N-cadherin proteins. Conclusions DNAJC1 had a predictive value for the prognosis of HCC. Knockdown of DNAJC1 may inhibit HCC cell proliferation, migration and invasion and promote the HCC cell apoptosis through p53 and EMT signaling pathways.
Keywords: Hepatocellular carcinoma; Bioinformatic analysis; DNAJC1